2019
DOI: 10.1177/2040622319891558
|View full text |Cite
|
Sign up to set email alerts
|

CircHECTD1 mediates pulmonary fibroblast activation via HECTD1

Abstract: Background:Circular RNA (circRNA), a new class of noncoding RNA, has been shown to be important in silicosis due to its unique role as a transcription regulator or as a sponge of small RNA regulators. Here, the mechanisms underlying circHECTD1/HECTD1 in fibroblast activation and subsequent fibrosis induced by SiO2 were investigated.Methods:Primary human pulmonary fibroblasts (HPF-a) were utilized, combined with quantitative real-time PCR (qRT-PCR) and fluorescence in situ hybridization (FISH) assays. LC3B-LV-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 51 publications
2
23
0
Order By: Relevance
“…Moreover, circRNAs are stable and widely expressed in many tumor tissues [14,15]. Some circRNAs have important biological functions and can be considered as biomarkers for diagnosis of multiple diseases [4,16,17]. This suggests the possibility that circRNAs, like miRNAs, may be involved in paracrine signaling or cell-to-cell crosstalk.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, circRNAs are stable and widely expressed in many tumor tissues [14,15]. Some circRNAs have important biological functions and can be considered as biomarkers for diagnosis of multiple diseases [4,16,17]. This suggests the possibility that circRNAs, like miRNAs, may be involved in paracrine signaling or cell-to-cell crosstalk.…”
Section: Discussionmentioning
confidence: 99%
“…circHECTD1 was upregulated in the mouse model of silicosis. Their studies included the direct role of circHECTD1/HECTD1 axis in fibroblast [ 81 ] and its indirect effect through endothelial cells [ 82 ] and macrophages [ 83 ], leading to induction of lung fibrosis after stimulation with SiO. An additional study by the same group confirmed the role of circ_012091 in mediating the silicosis-induced lung fibrosis as it was downregulated in the mouse model of silicosis and after induction of lung cells with SiO in vitro [ 35 ].…”
Section: Circrna and Oxs In The Lungmentioning
confidence: 99%
“…In primary human pulmonary fibroblasts (HPF-a) exposed to SiO, circHECTD1 was downregulated, thus inducing an increase in HECTD1, which subsequently caused fibroblast activation and accumulation via the EMT and endothelial-mesenchymal transition (EndMT) processes [97,103,104]. CircRNAs also help fibroblasts overcome stress.…”
Section: Circrna and Cancer-associated Fibroblasts (Cafs)mentioning
confidence: 99%